PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Kasus Organisasi Pemerintah Daerah Pada Kabupaten Rokan Hilir) - Nurul Fathia; Amries Rusli Tanjung; Novita Indrawati (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
Financial statement is a structural presentation from financial position and financialperformance of the entity. The purpose of financial statement is to give informationabout financial position, financial performance and entity cash flow to give benefitsfor the user of financial statement.This study has several objectives: first, to examinethe role of internal control system in financial statement quality. Second, to examinethe role of information technology utilization in financial statement quality. Third, toexamine the role of human resources competency in the financial statement qualityand the effect of organizational commitment as variable moderation. Data isobtained from the quistionaires from 115 respondent from 25 OPD in KabupatenRokan Hilir . Using SPSS 21 the results of this study show that internal controlsystem, information technology utilization and human rources competency has aninfluence on financial statement quality. The results of this study confirmcommitment organization only effected relationship between internal control systemwith financial statement quality.